The Sound of Scotoma: Audio Space Representation Reorganization in Individuals With Macular Degeneration - Ahmad, Hafsah; Setti, Walter; Campus, Claudio; Capris, Elisabetta; Facchini, Valentina; Sandini, Giulio; Gori, Monica (Frontiers in Integrative Neuroscience, 2019)
Blindness is an ideal condition to study the role of visual input on the development of spatial representation, as studies have shown how audio space representation reorganizes in blindness. However, how spatial reorganization works is still unclear. A limitation of the study on blindness is that it is a “stable” system and it does not allow for studying the mechanisms that subtend the progress of this reorganization. To overcome this problem here we study, for the first time, audio spatial reorganization in 18 adults with macular degeneration (MD) for which the loss of vision due to scotoma is an ongoing progressive process. Our results show that the loss of vision produces immediate changes in the processing of spatial audio signals. In individuals with MD, the lateral sounds are “attracted” toward the central scotoma position resulting in a strong bias in the spatial auditory percept. This result suggests that the reorganization of audio space representation is a fast and plastic process occurring also later in life, after vision loss.